A study on the genus Stenus Latreille from Shenzhen City of Guangdong, South China (Coleoptera, Staphylinidae) - Tang, Liang; Xu, Wang; Xia, Mei-Hua (Zootaxa, 2019)
The species of the genus Stenus Latreille from Shenzheng city, Guangdong, South China, are studied. A new species is described under the name: Stenus wutongshanus sp. n. Five species, Stenus tenuipes Sharp, 1874, Stenus abdominalis abdominalis Fauvel, 1895 Stenus bivulneratus Motschulsky, 1857, Stenus stigmatias Puthz, 2008 and Stenus spurius L. Benick, 1929, are newly recorded to Guangdong. Diagnostic characters of the new species are illustrated and a key to species of Shenzheng city is provided.